Expression of the transient receptor potential channels TRPV1, TRPA1 and TRPM8 in mouse trigeminal primary afferent neurons innervating the dura - Huang Dongyue; Li Shuyang; Dhaka Ajay; Story Gina M; Cao Yu-Qing (SAGE Publishing, 2012)
Abstract Background Migraine and other headache disorders affect a large percentage of the population and cause debilitating pain. Activation and sensitization of the trigeminal primary afferent neurons innervating the dura and cerebral vessels is a crucial step in the "headache circuit". Many dural afferent neurons respond to algesic and inflammatory agents. Given the clear role of the transient receptor potential (TRP) family of channels in both sensing chemical stimulants and mediating inflammatory pain, we investigated the expression of TRP channels in dural afferent neurons. Methods We used two fluorescent tracers to retrogradely label dural afferent neurons in adult mice and quantified the abundance of peptidergic and non-peptidergic neuron populations using calcitonin gene-related peptide immunoreactivity (CGRP-ir) and isolectin B4 (IB4) binding as markers, respectively. Using immunohistochemistry, we compared the expression of TRPV1 and TRPA1 channels in dural afferent neurons with the expression in total trigeminal ganglion (TG) neurons. To examine the distribution of TRPM8 channels, we labeled dural afferent neurons in mice expressing farnesylated enhanced green fluorescent protein (EGFPf) from a TRPM8 locus. We used nearest-neighbor measurement to predict the spatial association between dural afferent neurons and neurons expressing TRPA1 or TRPM8 channels in the TG. Results and conclusions We report that the size of dural afferent neurons is significantly larger than that of total TG neurons and facial skin afferents. Approximately 40% of dural afferent neurons exhibit IB4 binding. Surprisingly, the percentage of dural afferent neurons containing CGRP-ir is significantly lower than those of total TG neurons and facial skin afferents. Both TRPV1 and TRPA1 channels are expressed in dural afferent neurons. Furthermore, nearest-neighbor measurement indicates that TRPA1-expressing neurons are clustered around a subset of dural afferent neurons. Interestingly, TRPM8-expressing neurons are virtually absent in the dural afferent population, nor do these neurons cluster around dural afferent neurons. Taken together, our results suggest that TRPV1 and TRPA1 but not TRPM8 channels likely contribute to the excitation of dural afferent neurons and the subsequent activation of the headache circuit. These results provide an anatomical basis for understanding further the functional significance of TRP channels in headache pathophysiology.